Performance evaluation of pilot symbol assisted power control in CDMA systems - Sim, , ML; Chuah, , HT (2002)
Transmitter power control is an effective scheme to improve the performance of cellular DS/CDMA systems. In the reverse link, pilot symbols are used to assist the estimation of received signal power in order to improve the performance of power control. In this paper, we propose a model for the evaluation of the performance of a power-controlled reverse link CDMA system in the presence of Rayleigh flat fading. The model allows analysis of design parameters such as the number of pilot symbols, the power control updating frequency and the maximum allowable transmitted power. Analysis result shows that when transmitter power control is used, system capacity can be increased by more than 40% for typical normalised Doppler frequency in cellular communications.